2021
DOI: 10.3389/fpsyg.2021.633469
|View full text |Cite
|
Sign up to set email alerts
|

“He’s Just a Wee Laddie”: The Relative Age Effect in Male Scottish Soccer

Abstract: Significant structural, developmental, and financial constraints exist in Scottish soccer that may predicate a different approach to talent identification and development. To our knowledge, no published reports exist evaluating the prevalence of the relative age effect (RAE) in Scottish soccer players. Consequently, the aim of this study was to investigate the prevalence of the RAE among varied playing levels and ages of male Scottish youth soccer players. Birthdates of male youth players (n = 1,230) from U10 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
28
2
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(37 citation statements)
references
References 41 publications
6
28
2
1
Order By: Relevance
“…Moreover, a longitudinal investigation into the RAE in an English professional soccer club showed that Q4 male soccer players were approximately four times more likely to achieve adult professional status than Q1 player's, despite the reduced number of players within Q4 (Kelly et al, 2019). This reinforces the changes associated with the transition from youth to professional adult level, which has implications in the RAE, as reported by others (Brustio et al, 2018;Lupo et al, 2019;Dugdale et al, 2021).…”
Section: Discussionsupporting
confidence: 70%
See 3 more Smart Citations
“…Moreover, a longitudinal investigation into the RAE in an English professional soccer club showed that Q4 male soccer players were approximately four times more likely to achieve adult professional status than Q1 player's, despite the reduced number of players within Q4 (Kelly et al, 2019). This reinforces the changes associated with the transition from youth to professional adult level, which has implications in the RAE, as reported by others (Brustio et al, 2018;Lupo et al, 2019;Dugdale et al, 2021).…”
Section: Discussionsupporting
confidence: 70%
“…No comparisons with other studies are possible, as this is the first study reporting the RAE according to each club or academy classification level, which is attributed based on a specific certification process implemented by the FPF. Of note, when looking into the RAE on male Scottish youth soccer players, Dugdale et al (2021) showed an influence of the playing level within male soccer academy structures.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The relative age effect (RAE) is a demographic phenomenon involving a bias towards the selection of athletes born earlier in an age group year compared to those born later in the same year [2][3][4]. Further, the RAE is commonly observed in male invasion sports that require physical precocity, such as Australian football [3,5,6], basketball [7][8][9], ice hockey [10][11][12], rugby [13][14][15], and soccer [4,[16][17][18][19][20][21][22].…”
Section: Introductionmentioning
confidence: 99%